Analysis Of The Quality Of Electronic Service Es-Qual And E-Recs-Qual Models In The Bsi Mobile Application To The Level Of Customer Loyalty At Bsi Bank - Adinda Nur Syafina Putri; Zuhdan Ady Fataron; Nasrul Fahmi Zaki Fuadi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
AbstractPurpose - This study aims to analyze the electronic service model ES-Qual and E-Recs-Qual in the BSI Mobile application at the level of customer loyalty at the BSI bank KCP Kendal Weleri Central Java.Method - Research is a study that uses quantitative methods, with primary data from questionnaires filled out directly by customers. The population was 1.015, according to USAK data. The sample used was 85 respondents.Result - The results obtained in this study indicate the results of the simultaneous test of the eight variables significantly contributed. In partial test results, variables that have a positive and significant effect on the level of loyalty are efficiency variables, privacy, compensation, and compatibility of mobile device variables. While the variables of reliability, fulfillment, responsiveness, and contact do not have a significant influence on the level of customer loyalty.Implication - This research will have an impact on how to increase customer loyalty regarding the services provided by BSI bank in relation to the mobile banking application.Originality - This study analyzes the relationship between the electronic service variables of the ES-Qual and E-Recs-Qual models in the BSI Mobile application at the level of customer loyalty.